2018
DOI: 10.1177/1043659618786363
|View full text |Cite
|
Sign up to set email alerts
|

Early Care and Education Teacher’s Role in Obesity Prevention and Healthy Development of Young American Indian Children

Abstract: Teachers of tribally affiliated ECE centers are important stakeholders in promoting the health and well-being of young American Indian children. Additional efforts are needed to more effectively integrate teachers and nurses in order to create effective interventions. We propose a stakeholder partnership to guide the development of future interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…33 In the present focus groups, ECE providers acknowledged the shared responsibility and empathized with the parent’s constraints at home. Other qualitative research involving parent and ECE providers has found that ECE providers from ECE centers were empathetic to the parents’ busy lifestyle, 34 which may be due to the close connection of the ECE providers with parents within their community. Communication was not mentioned as frequently in the present sample but is another important part of creating a harmonious parent—ECE provider relationship as found in a recent systematic review of qualitative studies involving physical activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 In the present focus groups, ECE providers acknowledged the shared responsibility and empathized with the parent’s constraints at home. Other qualitative research involving parent and ECE providers has found that ECE providers from ECE centers were empathetic to the parents’ busy lifestyle, 34 which may be due to the close connection of the ECE providers with parents within their community. Communication was not mentioned as frequently in the present sample but is another important part of creating a harmonious parent—ECE provider relationship as found in a recent systematic review of qualitative studies involving physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…32 As the focus of this study was on child-level outcomes, these themes may not have emerged unlike in another qualitative study that specifically focused on collaboration between parents and ECE providers. 34 Therefore, understanding this shared responsibility is a promising step forward for parents and ECE providers to working together for child health.…”
Section: Discussionmentioning
confidence: 99%
“…A tailored training on the implementation of the best-practice menu and how to implement it amidst the challenges and barriers identified by the community took place in December 2017 at a tribal education facility. The training program itself was based on adult learner needs (Norris, 2003) and previously identified needs in knowledge (Sisson et al, 2018; Sisson et al, 2017; Kracht et al, 2019). The program was broken into smaller sections (i.e., six modules) with heavy emphasis on application and integration activities.…”
Section: Resultsmentioning
confidence: 99%
“…One study included educational materials tailored for ECE cooks with improved intent to use nutritional guidelines, but was insufficient to enhance menu quality (Yoong et al, 2016). Qualitative work conducted by our own team indicates that teachers and providers desire to know more about child nutrition and health behaviors than the basic guidelines for menu development provided to them during routine trainings (Sisson et al, 2018; Sisson et al, 2017; Kracht et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Study design and methods are detailed in the sister paper focusing on the ECE teachers (Kracht et al, 2018). In brief, this qualitative study involved 60 individual interviews with 20 interviews per the three main stake holders: ECE teachers of AI children, HCPs who serve young AI children, and parents of AI children.…”
Section: Methodsmentioning
confidence: 99%